Os arquétipos femininos nos contos de fadas clássicos e nas versões contemporâneas - Lobão, Geórgia Linhares Carneiro (2023)
The research object of study is the representation of the feminine present in versions of fairy tales in cordel, in their classic versions and in contemporary versions. The general objective is to investigate changes in such representation in the archetypes present in different versions of fairy tales, through semiotic analysis. Its specific objectives are: to compare the archetypes of the feminine in the versions of the story Beauty and the Beast; compare the construction of gender meaning in the short story The Little Mermaid, considering the classic version and national reinterpretations, including in cordel; understand the changes in gend er archetypes, through semiotic metalinguistic instruments, in different versions of the classic fairy tales Beauty and the Beast and The Little Mermaid. The theoretical foundations that anchor this work will be based on studies on gender issues. The studies are based on authors such as Jung (1977) and Frye (2000), with regard to archetypes, an essential concept for identifying how identities and their representations are constructed in these narratives. Studies on gender issues are approached from the theo retical perspective of Beauvoir (1949) and Lacan (1988), two essential precursors to understanding the first and most established theories on the study of gender. Beauvoir defends the theory of gender study as a social construction; Lacan already establish es another aspect, the theory of the relationship of objects. These theories, although divergent, have a lot of influence in this field of study, showing their enormous variations and possibilities. Studies on popular literature are based on Propp (1984), Albuquerque (2011), Saraiva (2004) and Câmara Cascudo (1939), responsible for exploring both theory and historical values, (2004) and Câmara Cascudo (1939), responsible for exploring both theory and historical values, which is fundamental to understanding its importance both literary and social. Different versions of which is fundamental to understanding its importance both literary and social. Different versions of fairy tales are analyzed, through varied works, from the most classic, such as that of the Grimm brothers, Charles Perrault, as well as Madame de Beaumont and Madame de Villeneuve (responsible for the two most famous versions of Beauty and the Fera), from the new versions inspired by fairy tales, by Clara Savelli and Louise O'Neill, to the cordel version, by professor Stélio Torquato.